2017
DOI: 10.36104/amc.2016.727
|View full text |Cite
|
Sign up to set email alerts
|

Tratamiento hipolipemiante y su efectividad en pacientes de cuatro ciudades colombianas, 2012-2013.

Abstract: Introducción. La prevalencia de enfermedad cardiovascular ha aumentado, la hipercolesterolemia se ha asociado como factor de riesgo y se desconoce en algunas poblaciones cuántos pacientes logran el control metabólico. Objetivo: Determinar la efectividad del tratamiento hipolipemiante en pacientes afiliados al Sistema de Salud Colombiano. Métodos. Estudio de corte transversal para determinar la efectividad del tratamiento hipolipemiante, en una muestra aleatoria de 211 pacientes adultos tratados con estatinas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
3
3
0
3
Order By: Relevance
“…This change towards increased atorvastatin prescriptions is also supported by previous national study results, which found that patients treated with lovastatin were less likely to achieve metabolic control (although it was used at doses lower than those recommended, similar to the present study) 8 . In addition, atorvastatin has been identified as the most cost-effective option for patients with dyslipidemia in the Colombian health context when moderate to high intensity treatments are required 14 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This change towards increased atorvastatin prescriptions is also supported by previous national study results, which found that patients treated with lovastatin were less likely to achieve metabolic control (although it was used at doses lower than those recommended, similar to the present study) 8 . In addition, atorvastatin has been identified as the most cost-effective option for patients with dyslipidemia in the Colombian health context when moderate to high intensity treatments are required 14 .…”
Section: Discussionsupporting
confidence: 91%
“…More molecules are now available in all lipid-lowering drug groups, and reports in Colombian populations show some changes in their prescriptions. For example, by the year 2013, atorvastatin had already displaced lovastatin as the most widely used statin drug 7 , 8 .…”
mentioning
confidence: 99%
“…El grupo farmacológico sobre el que se centraron la mayor cantidad de las investigaciones revisadas corresponde a los principios activos indicados para la reducción de los niveles de lípidos plasmáticos, seguido de los antiinflamatorios no esteroideos (AINES). En Colombia, el Instituto Nacional de Salud, por medio de la Encuesta nacional de situación nutricional realizada en el 2015, estableció que la principal causa de muerte en el país corresponde a enfermedad cardiovascular [84], además, diversos estudios han mostrado una alta prevalencia de los factores de riesgo cardiovasculares, entre los cuales la dislipidemia alcanza un 35,7% [85]. Por su parte, los AINES están incluidos en el grupo de medicamentos con mayor venta en el país y existen alrededor de cuatro mil registros sanitarios para productos que contienen algún AINES en su composición.…”
Section: Principio Activounclassified
“…Additionally, the most frequent dyslipidemias are mixed, in which the components of hypertriglyceridemia and low HDL cholesterol (HDL-C) are key reasons for seeking combined therapy with fibrates and statins. 9,10 977733J PCXXX10.1177/2150132720977733Journal of Primary Care & Community HealthMachado-Duque et al research-article2020 1 Universidad Tecnológica de Pereira-Audifarma S.A., Pereira, Colombia 2 Grupo Biomedicina, Fundación Universitaria Autónoma de las Américas, Pereira, Colombia Some meta-analyses have shown a modest impact of fibrates on cardiovascular disease, as well as the safety profile of the combination of rosuvastatin + fenofibric acid, which does not increase the incidence of muscle-related adverse events, rhabdomyolysis, or liver complications, making it a safe therapeutic option for the management of mixed dyslipidemias. [11][12][13] The Colombian Health System offers universal coverage to the population through affiliation with 1 of 2 regimes, the contributory regime paid by the employer and the statesubsidized regime.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the most frequent dyslipidemias are mixed, in which the components of hypertriglyceridemia and low HDL cholesterol (HDL-C) are key reasons for seeking combined therapy with fibrates and statins. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%